Determinants of Earnings Management in Food and Beverage Sector Companies in Indonesian - Ummy Kalsum; Muhammad Nur; Rince Tambunan; La Ode Hamida; Rahmatia Rahmatia (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This research aims to provide evidence that leverage, managerial ownership, board of directors, and firm size affect earnings management. The type of research used in this research is quantitative research with a descriptive approach. The population in this study is all manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange, which are 18 companies and disclose annual reports for 2017-2021. The data collection technique used in this study is more precisely using the purposive sampling technique so that the researcher will take 45 samples from the population. This study found that leverage, managerial ownership, and firm size positively and significantly affect earnings management. In contrast, the board of directors has a negative and insignificant effect on earnings management.